A1 COLONOSCOPY FINDINGS FOLLOWING A FECAL IMMUNOCHEMICAL TEST: A RETROSPECTIVE STUDY ASSESSING THE SCREENING TEST PERFORMANCE. (26th February 2020) - Delisle, M; Tremblay-Sirois, L; Proulx, M; Trottier-Tellier, F; Martel, M; Ménard, C
Abstract: Background: Fecal Immunochemical Testing (FIT) is the preferred test for colorectal cancer screening in the average risk population in Canada. Aims: This study aims to assess colonoscopy findings in patients who have undergone a FIT within the previous 2 years. Methods: This retrospective study included all adult patients that have undergone a single diagnostic colonoscopy from March 2013 to March 2016 following a single FIT test at the CIUSSS de l'Estrie, a tertiary hospital. The primary outcome was to evaluate rates of clinically significant lesion when comparing FIT positive (FIT+) to FIT negative (FIT-) colonoscopy, using Quebec's current threshold of 175 ng/ml of hemoglobin. Secondary outcomes included all other type of lesions, delays between FIT testing and colonoscopy, procedural time, caecal intubation rates and withdrawal time. Results: Overall, 2230 patients were included, aged 62.0±10.5 years, 55.0% were female and 26.1% had a positive FIT. Patients with a positive FIT had a significantly higher polypectomy rate (62.4% vs 41.3%, p<0.01) and higher number of polyps per patient (2.9±2.5 vs 2.1±1.5, p<0.01). FIT+ had significantly higher rates of adenocarcinoma (3.4% vs 0.7%, p<0.01) with 11 out of 31 patients bearing a negative FIT with the current threshold. No difference was found for sessile serrated polyps (7.8% vs 6.0%, p=0.13). Patients with a FIT+ had significantly higher advanced adenomas (24.0% vs 5.6%, p<0.01), proximal polyps (33.6% vs 22.4%, p<0.01), distal polyps (52.8% vs 28.2%, p<0.01), non-advanced adenomas (38.5% vs 23.9%, p<0.01) and benign polyps (25.1% vs 17.2%, p<0.01). Patients with FIT+ received their colonoscopy 7.5 months earlier than FIT- patients (3.3±2.2 vs 10.8±8.3 months, p<0.01). FIT+ also yielded a significant longer procedural time (28.5±14.1 vs 25.5±12.1, p<0.01) but no difference was noted for caecal intubation rates and withdrawal time (93.3% vs 94.0%, p=0.55 and 14.0±8.4 vs 12.0±7.7, p=0.20 respectively). Results were similar when lowering the threshold to 150, 100, 75 and even 50 ng/ml. 8 patients with an adenocarcinoma had a FIT level lower than 50 ng/ml. Conclusions: Patients with a colonoscopy and a positive FIT have higher rates of significant findings. Although commonly used for colorectal cancer screening, FIT still failed to detect almost 30% of adenomas and adenocarcinomas found during colonoscopy. It also does not perform very well for serrated polyps. Our data also fails to show an improved yield of the FIT when lowering the its threshold from 175 to 50. There is still a great need for a more sensitive non-invasive colon cancer screening test. Funding Agencies: None